ANALISIS MISKONSEPSI PESERTA DIDIK KELAS VII PADA MATERI BILANGAN RASIONAL BERDASARKAN JAWABAN TES URAIAN - Oktri Khairani; Sri Yunita Ningsih (Ensiklopedia Research and Community Service Review, 2026)
This study aims to analyze the misconceptions of seventh-grade students on rational numbers material based on essay test answers. The research employed a descriptive qualitative approach involving 32 seventh-grade students of MTs Nurul Falah Airmolek as research subjects. The instrument used was an essay test consisting of four questions designed based on indicators of conceptual understanding, namely restating concepts, classifying rational and irrational numbers, representing fractions into decimals, and applying rational number operations in contextual problems. Data were analyzed using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results showed that students still experienced relatively high misconceptions in rational numbers material. The highest error percentage occurred in the indicator of applying rational number operations in contextual problems (68.75%). The most dominant type of misconception was Concept Errors (Co), with the highest percentage reaching 56.25%, indicating that most student errors were caused by a lack of conceptual understanding rather than procedural inaccuracy. These findings indicate that students’ understanding of rational numbers concepts is still not optimal. Therefore, more innovative and constructivist learning strategies emphasizing conceptual understanding, multiple mathematical representations, and contextual exercises are needed to minimize misconceptions.Keywords: Misconception; Rational numbers; Essay test; Conceptual understanding.